MEKANISME SOSIAL DAN KETAHANAN LINGKUNGAN DALAM MENJAGA KETERTIBAN KOMUNITAS HUKUM ADAT SUKU MAKIYAN DI MALUKU UTARA - Falsafah Nur Aini; Eva Dina Bella Septina; Fathur Rohman Devin Al Djupri; Riefany Rizky Noorrachman (Pojok Publisher, 2025)
This study examines the social mechanisms and environmental resilience in the customary law system of the Makiyan Tribe in North Maluku. Customary law, as an integral part of the community's culture, plays a role in regulating social relations and protecting the environment through rules that are passed down from generation to generation. The Makiyan Tribe, with a customary leadership structure involving soa (customary leaders) and toma ne (customary elders), applies customary norms to maintain social order and environmental sustainability. This study uses a qualitative approach with a literature study research method to explore the role of customary law in facing the challenges of modernization, exploitation of natural resources, and the inconsistency between state regulations and customary law. The results of the study indicate that although customary law remains the foundation of social order and environmental management, there are major threats coming from national policies that do not accommodate the rights of indigenous peoples and industrial expansion. Modernization and social change, especially among the younger generation, also influence the implementation of customary law. This study suggests the need for harmonization between customary law and state law to create an inclusive legal system, as well as the importance of recognizing the customary rights of indigenous peoples in national policies.